Social business: a response to the new global economic reform - Yunus, Muhammad (Revista Española de Desarrollo y Cooperación, 2023)
Despite the economic development and prosperity achieved around the world during the last decades, poverty continues being a significant challenge to tackle. The article points out the need of a major change in the financial framework of capitalism that allow poor people to gain economic empowerment and therefore, access to better life conditions. This can be achieved through social businesses, which are those that exist for the collective benefit of others. The article offers examples of social business, including the case of the Grameen Bank in Bangladesh, as well as different ways to design this type of businesses, stressing out the importance of information technology, as an effective way to spread out this innovative idea.